Identifying the Sources of Intestinal Colonization With Extended-Spectrum β-Lactamase-Producing Escherichia coli in Healthy Infants in the Community - Amin, Mohammed Badrul; Hoque, Kazi Injamamul; Roy, Subarna; Saha, Sumita Rani; Islam, Md. Rayhanul; Julian, Timothy R.; Islam, Mohammad Aminul (Frontiers in Microbiology, 2022)
The prevalence of fecal colonization with extended spectrum β-lactamase-producing Escherichia coli (ESBL-Ec) among children in low- and middle-income countries is alarmingly high. This study aimed to identify the sources of ESBL-Ec colonization in children <1-year-old through comparative analysis of E. coli isolates from child stool (CS), child’s mother stool (MS), and point-of-use drinking water (WU) from 46 rural households in Bangladesh. Pairwise similarity in antibiotic susceptibility (AS) of E. coli from all three sources was evaluated followed by phylogenetic clustering using Enterobacterial Repetitive Intergenic Consensus PCR (ERIC-PCR) and whole genome sequence analysis of the isolates. Matching AS and ERIC-PCR patterns were found among ESBL-Ec isolates from child-mother dyads of 24 and 11 households respectively, from child-water dyads of 5 and 4 households respectively, and from child-mother-water triads of 3 and 4 households respectively. WGS analysis of 30 isolates from 10 households revealed, ESBL-Ec from children in 5 households (50%) were clonally related to ESBL-Ec either from their mothers (2 households), drinking water sources (2 households) or both mother and drinking-water sources (1 household) based on serotype, phylogroup, sequence type, antibiotic resistance genes, mobile genetic elements, core single nucleotide polymorphisms and whole genome multi locus sequence typing (wgMLST). Overall, this study provides empirical evidence that ESBL-Ec colonization in children is linked to the colonization status of mothers and exposure to the household environments contaminated with ESBL-Ec. Interventions such as improved hygiene practices and safe drinking water supply may help reduce the transmission of ESBL-Ec at household level.